2015
DOI: 10.1186/s13058-015-0562-7
|View full text |Cite
|
Sign up to set email alerts
|

Podocalyxin enhances breast tumor growth and metastasis and is a target for monoclonal antibody therapy

Abstract: IntroductionPodocalyxin (gene name PODXL) is a CD34-related sialomucin implicated in the regulation of cell adhesion, migration and polarity. Upregulated expression of podocalyxin is linked to poor patient survival in epithelial cancers. However, it is not known if podocalyxin has a functional role in tumor progression.MethodsWe silenced podocalyxin expression in the aggressive basal-like human (MDA-MB-231) and mouse (4T1) breast cancer cell lines and also overexpressed podocalyxin in the more benign human bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 36 publications
4
70
1
Order By: Relevance
“…Contrasting with these data, in the breast cancer cell lines MDA-MB-231, the highly aggressive MDA-MB-231 clone 4175 and NAMEC8R, all expressing high levels of endogenous PODXL, silencing of PODXL exerted no effect on cell proliferation under monolayer culture conditions [80][81][82]. However, the frequency of tumorsphere-forming cells was markedly decreased in PODXL-silenced MDA-MB-231 breast cancer cell line and, conversely, its overexpression in luminal-like MCF-7 breast cancer cell line, a low metastatic cell line expressing low levels of endogenous PODXL, resulted in increased tumorsphere formation [80]. Consistent with these results, silencing of PODXL in MDA-MB-231 cells reduced primary tumor growth in a mouse model xenograft [80,82].…”
Section: Burkitt Lymphoma Raji Ectopic Overexpression Of Podxlcontrasting
confidence: 67%
See 1 more Smart Citation
“…Contrasting with these data, in the breast cancer cell lines MDA-MB-231, the highly aggressive MDA-MB-231 clone 4175 and NAMEC8R, all expressing high levels of endogenous PODXL, silencing of PODXL exerted no effect on cell proliferation under monolayer culture conditions [80][81][82]. However, the frequency of tumorsphere-forming cells was markedly decreased in PODXL-silenced MDA-MB-231 breast cancer cell line and, conversely, its overexpression in luminal-like MCF-7 breast cancer cell line, a low metastatic cell line expressing low levels of endogenous PODXL, resulted in increased tumorsphere formation [80]. Consistent with these results, silencing of PODXL in MDA-MB-231 cells reduced primary tumor growth in a mouse model xenograft [80,82].…”
Section: Burkitt Lymphoma Raji Ectopic Overexpression Of Podxlcontrasting
confidence: 67%
“…However, the frequency of tumorsphere-forming cells was markedly decreased in PODXL-silenced MDA-MB-231 breast cancer cell line and, conversely, its overexpression in luminal-like MCF-7 breast cancer cell line, a low metastatic cell line expressing low levels of endogenous PODXL, resulted in increased tumorsphere formation [80]. Consistent with these results, silencing of PODXL in MDA-MB-231 cells reduced primary tumor growth in a mouse model xenograft [80,82]. Nevertheless, no effect of PODXL silencing on tumor growth was observed when the xenografted cell lines were MDA-MB-231 clone 4175 cells, NAMEC8R, or the pancreatic cancer cell lines SW1990 and Pa03c [81,83].…”
Section: Burkitt Lymphoma Raji Ectopic Overexpression Of Podxlmentioning
confidence: 93%
“…Our results suggest that targeting PODXL might be a novel strategy for the treatment of lung adenocarcinoma. In this regard, there has been some recent progress towards the development of PODXL‐targeted therapies, including PODXL‐targeted monoclonal antibody therapy to inhibit primary tumor growth and systemic dissemination of breast cancer . In addition, Chijiiwa et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, there has been some recent progress towards the development of PODXL-targeted therapies, including PODXL-targeted monoclonal antibody therapy to inhibit primary tumor growth and systemic dissemination of breast cancer. (33) In addition, Chijiiwa et al (34) suggest that miR-5100, which directly binds to the 3 0 untranslated region of the PODXL transcript and downregulates PODXL expression, could have therapeutic potential for the treatment of metastatic pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PODXL was previously reported to enhance tumor aggressiveness in breast cancer, prostate cancer, oral squamous cell carcinoma and astrocytoma (56)(57)(58)(59). hsu et al reported PODXL-ebP50-ezrin molecular complex enhances the metastatic potential of renal cancer through recruiting RAC1 guanine nucleotide exchange factor, ARhgeF7 (60).…”
Section: Discussionmentioning
confidence: 99%